Anterior lead location predicts verbal fluency decline following STN-DBS in Parkinson's disease. (November 2021) - Greif, Taylor R.; Askari, Asra; Cook Maher, Amanda; Patil, Parag G.; Persad, Carol
Abstract: Introduction: Verbal fluency (VF) decline is a well-documented cognitive effect of Deep Brain Stimulation of the subthalamic nucleus (STN-DBS) in patients with Parkinson's disease (PD). This decline may be associated with disruption to left-sided frontostriatal circuitry involving the anteroventral non-motor area of the STN. While recent studies have examined the impact of lead location in relation to functional STN subdivisions on VF outcomes, results have been mixed and methods have been limited by atlas-based location mapping. Methods: Participants included 59 individuals with PD who underwent bilateral STN-DBS. Each participant's active contact location was determined in an atlas-independent fashion, relative to their individual MR-visualized STN midpoint. Multiple linear regression was used to examine lead location in each direction as a predictor of phonemic and semantic VF decline, controlling for demographic and disease variables. Results: More anterior lead locations relative to the STN midpoint in the left hemisphere predicted greater phonemic VF decline (B = −2.34, B SE = 1.08, β  = −0.29, sr 2  = 0.08). Lead location was not a significant predictor of semantic VF decline. Conclusion: Using an individualized atlas-independent approach, present findings suggest that more anterior stimulation of the left STN may uniquely contribute to post-DBS VF decline. This is consistent with models in which the anterior STN represents a "non-motor" functional subdivision with connections to frontal regions, e.g., the left dorsal prefrontal cortex. Future studies should investigate the effect of DBS lead trajectory on VF outcomes. Highlights: Atlas-independent methods more fully account for individual anatomical variability. This individualized approach can more precisely measure DBS lead location. More anterior STN lead location predicts post-DBS phonemic verbal fluency decline. Anterior STN stimulation may disrupt non-motor (cognitive) frontostriatal networks.